Evaluating the implementation of a memory clinic using the RE‐AIM model: The experience of the "memory and neuropsychiatry clinic" in Hospital Del Salvador, Chile: Health services research / Services. (7th December 2020) - Leon, Tomas; Castro, Loreto; Mascayano, Franco; Lawlor, Brian; Slachevsky, Andrea
Abstract: Background: The prevalence of dementia in Chile is 1.06%, meaning that over 200, 000 people are affected. In 2017, the Ministry of Health launched the National Plan of Dementia in Chile which proposed establishing a range of health‐care services from primary care to Memory Units (MU). MUs have emerged as a new health care service composed of multidisciplinary teams with the goal of improving diagnosis and/or management of dementia patients. The creation and implementation of an MU should take into consideration policies and the organization of a particular healthcare system. In this context, the evaluation of a Chilean MU might provide information for the standardization and replication of such a health service nationwide. The objective of this paper was to evaluate the implementation processes of an MU using the RE‐AIM model, a multi‐component model aimed to assist the evaluation of the implementation of ongoing programs. Method: We analyze the interventions made during the MU lifespan using the RE‐AIM model, a multi‐component model useful in evaluating the implementation of ongoing programs Result: From March 2018 up to June 2019, a total of 510 patients were referred and assessed at the Hospital del Salvador, Santiago, Chile. Most patients came from primary care (51.9%) and from outpatient services at the Hospital (39.2%), particularly from the Neurology (63.3%) and Psychiatry (16.0%) departments. We estimated that MU assessed 5.39% of dementia patients in the referring area. Of all the patients evaluated by the MU, 11.11% were discharged. Of these, 66.1% were referred to primary health care, 16.94% to other outpatient services, 10.16% to a specialized mental health care centre, and 6.77% % to a daycare centre. Conclusion: This was the first evaluation of the implementation of an MU as part of the Plan. It showed that it is possible to implement an MU in a low‐middle income country and improve access to dementia diagnosis, management, and treatment. Ongoing challenges include continuing to collect clinical data, creating research projects as part of the MU, and developing an MU protocol that can be adopted elsewhere in Chile.